Coexpression of binding sites for A(B) histo-blood group trisaccharides with galectin-3 and Lag antigen in human Langerhans cells - Smetana, K; Holíková, Z; Klubal, R; Bovin, N V; Dvoránková, B; Bartůnková, J; Liu, F T; Gabius, H J (Journal of leukocyte biology, 1999)
Galectin-3 is an immunomodulatory protein with binding capacity for various glycoconjugates including IgE. It has been shown to be produced by epidermal keratinocytes and is present on the surfaces of skin Langerhans cells (LC). Therefore, it may have a role in the pathogenesis of various skin diseases, such as atopic dermatitis. To study the expression of galectin-3 in LC, we used, in addition to specific antibodies, a panel of synthetic, carrier-immobilized, specific oligosaccharides of the A- and B-histo-blood group, which are recognized by this lectin. In the mean time, Birbeck granules were visualized with an anti-Lag antibody. The double labeling experiments showed a remarkable colocalization of signals for Lag antigen (Birbeck granules) and galectin-3, as well as the binding sites for A- and B-histo-blood group trisaccharides. The specificity of the oligosaccharide binding was demonstrated by the lack of binding by Le(c), Le(d) (H blood group antigen), and sLe(x), which are not recognized by galectin-3. These results suggest that galectin-3 is present in Birbeck granules, where it retains reactivity for its glycoligands.
Keywords: galektin 3; trisacharidy; Humans; lidé; ABO Blood-Group System; Trisaccharides; Langerhans Cells; protilátky; Galectin 3; Antibodies; Cytoplasmic Granules; ABO systém krevních skupin; vazebná místa; Langerhansovy buňky; cytoplazmatická granula; Antigens, Differentiation; Binding Sites; diferenciační antigeny